Neurons in the Pigeon Nidopallium Caudolaterale Display Value-Related Activity - Dykes, Madeline (Sci Rep, 2018)
We recorded from neurons in the nidopallium caudolaterale, the avian equivalent of the mammalian prefrontal cortex, in four birds. The birds were required to peck a stimulus that indicated the amount of reward they would receive (small or large) after a certain delay (short or long). We found that the activity of neurons in the nidopallium caudolaterale was modulated by the value of the reward that would be received based on the reward amount and the delay to reward. We found that value coding was most prominent during the presentation of the sample period, and less so during the delay period and during the presentation of the reward itself. Our findings support the view that activity in nidopallium caudolaterale reflects the encoding of the value of reward based on a combination of reward amount and delay to a reward.